2017
DOI: 10.1177/0954405417728313
|View full text |Cite
|
Sign up to set email alerts
|

A contribution for increasing workpiece location accuracy in a 3-2-1 fixture system

Abstract: The 3-2-1 fixture design principle is the most used method to locate prismatic workpieces. To further increase location accuracy, the influence of friction and contact stiffness between workpiece and fixture parts should be minimized. This can be achieved by decreasing the structural stiffness of the locators in the tangential direction to the contact. Hence, based on flexure hinges, locators with two different stiffness values are investigated. To analyze the influence of locator stiffness, a special experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Filho et al 16 proposed a novel approach to increase the position and orientation accuracy of the workpiece in the fixture with a 3-2-1 locating system by reducing the tangential stiffness of the locators. Parvaz and Nategh 17 used reaction force values to predict jamming occurrence conditions in the fixture design application.…”
Section: Introductionmentioning
confidence: 99%
“…Filho et al 16 proposed a novel approach to increase the position and orientation accuracy of the workpiece in the fixture with a 3-2-1 locating system by reducing the tangential stiffness of the locators. Parvaz and Nategh 17 used reaction force values to predict jamming occurrence conditions in the fixture design application.…”
Section: Introductionmentioning
confidence: 99%
“…They calculated the displacement of the workpiece relative to the fixture elements. Filho et al 30 investigated the effect of friction and stiffness of the contact between the workpiece and the fixture components, and by comparing the use of two types of rigid and flexible locators (with different structural stiffness in the tangential direction), showed that the displacement of the workpiece and its orientation are a function of clamping force but by reducing the tangential stiffness of the locator, the position and orientation accuracy of the workpiece can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional six-point locating principle is to set three, two, and one positioning points on the primary datum, secondary datum, and tertiary datum respectively to limit the six degrees of freedom of the workpiece. 6 Although this locating principle can satisfy the positioning requirements of the workpiece, it is only applicable to rigid parts and is not valid for flexible thin-walled parts. 7,8 The main problem for flexible thin-walled parts manufacturing is the deformation in the normal direction caused by the machining load and the workpiece weight.…”
Section: Introductionmentioning
confidence: 99%